Reviewing School Uniform through a Public Health Lens: Evidence about the Impacts of School Uniform on Education and Health - Johanna Reidy (Frontiers Media S.A., 2021)
This study uses a public health lens to review evidence about the impacts of wearing a school uniform on students' health and educational outcomes. It also reviews the underlying rationales for school uniform use, exploring historical reasons for uniform use, as well as how questions of equity, human rights, and the status of children as a vulnerable group are played out in debates over school uniforms. The literature identified indicates that uniforms have no direct impact on academic performance, yet directly impact physical and psychological health. Girls, ethnic and religious minorities, gender-diverse students and poorer students suffer harm disproportionately from poorly designed uniform policies and garments that do not suit their physical and socio-cultural needs. Paradoxically, for some students, uniform creates a barrier to education that it was originally instituted to remedy. The article shows that public health offers a new perspective on and contribution to debates and rationales for school uniform use. This review lays out the research landscape on school uniform and highlights areas for further research.